PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V UPTD SDN 122371 PEMATANGSIANTAR - Evelyn Simamora; Eva Pasaribu; Natalina Purba (STKIP Subang, 2025)
This study aims to investigate the effect of the Problem Based Learning (PBL) model on students' learning outcomes in the Science and Social Studies (IPAS) subject for fifth-grade students at UPTD SDN 122371 Pematangsiantar. The study employed a One-Group Pretest-Posttest design within a quantitative quasi- experimental approach, involving a population of 23 fifth-grade students. The research instrument used was a multiple-choice test to measure students' learning outcomes. Statistical analysis results showed that the implementation of the PBL model significantly improved learning outcomes, with a t-value of 15.822 exceeding the t-table value of 2.074 (df = 23, α = 0.05) and a significance level of 0.000 (<0.05). Correlation analysis yielded a correlation coefficient of 0.733, surpassing the critical r-value of 0.433 (df = 21, α = 0.05), indicating a strong relationship between PBL implementation and learning outcomes. Thus, the null hypothesis (H₀ ) was rejected, and the alternative hypothesis (Hₐ) was accepted, concluding that the PBL model significantly enhances students' learning outcomes in the IPAS subject during the Odd Semester of the 2025/2026 Academic Year.